Anatomical Connectivity-Based Strategy for Targeting Transcranial Magnetic Stimulation as Antidepressant Therapy - Tao, Qi; Yang, Yongfeng; Yu, Hongyan; Fan, Lingzhong; Luan, Shuxin; Zhang, Lei; Zhao, Hua; Lv, Luxian; Jiang, Tianzi; Song, Xueqin (Frontiers in Psychiatry, 2020)
Objectives: Abnormal activity of the subgenual anterior cingulate cortex (sACC) is implicated in depression, suggesting the sACC as a potentially effective target for therapeutic modulation in cases resistant to conventional treatments (treatment-resistant depression, TRD). We hypothesized that areas in the prefrontal cortex (PFC) with direct fiber connections to the sACC may be particularly effective sites for treatment using transcranial magnetic stimulation (TMS). The aim of this study was to identify PFC sites most strongly connected to the sACC. Methods: Two neuroimaging datasets were used to construct anatomic and functional connectivity maps using sACC as the seed region. Dataset 1 included magnetic resonance (MR) images from 20 healthy controls and Dataset 2 included MR images from 15 TRD patients and 15 additional healthy controls. PFC voxels with maximum values in the mean anatomic connection probability maps were identified as optimal sites for TMS. Results: Both right and left PFC contained sites strongly connected to the sACC, but the coordinates (in Montreal Neurological Institute space) of peak anatomic connectivity differed slightly between hemispheres. The left PFC site connected directly to the sACC both anatomically and functionally, while the right PFC site was functionally connected to the posterior cingulate cortex (PCC). Conclusions: Both left and right PFC are functionally connected to regions implicated in depression, the sACC and PCC, respectively. These bilateral PFC sites may be effective TMS targets to treat TRD.